Psychoeducation Interventions for Parents and Teachers of Children and Adolescents with ADHD: a Systematic Review of the Literature - Dahl, Victoria; Ramakrishnan, Amrita; Spears, Angela Page; Jorge, Annlady; Lu, Janice; Bigio, Nina Abraham; Chacko, Anil (Journal of developmental and physical disabilities, 2020)
Attention Deficit Hyperactivity Disorder (ADHD) is the most common neuropsychiatric condition in childhood and adolescence. Psychoeducation has been recommended by different guidelines as an initial treatment for ADHD, however the effects of the intervention for reducing symptoms and improving other outcomes still need to be established. This systematic review investigated the magnitude of impact that psychoeducation interventions have on various outcomes in children with ADHD. A systematic review of articles published between 1990 and 2018 was conducted of treatment outcome studies that investigated the effects of psychoeducation programs on youth with ADHD and their families. The outcomes of included studies consisted of ten constructs related to child and family functioning. Analyses used Hedges’ g formula to calculate individual study and summary effect sizes. Thirteen studies met our criteria. Among the effect sizes that were analyzed, significant findings include moderate to large effects on ADHD symptom improvement as reported by parents and teachers ( g = 0. 787), parent/teacher and child knowledge about ADHD ( g = 1.037 and g = 0. 721, respectively). Among the outcomes assessing child’s family and social functioning, effect sizes – as reported by parents, teachers, children/adolescents, and clinicians – were moderate to small. A few outcomes, including parenting stress and quality of life, were found to have small to no effects. Overall, this systematic review found the effects of psychoeducation as an intervention led to improvement in ADHD symptoms and behavioral problems, as reported by parents – potentially as a result of parents’ greater knowledge about how ADHD influences their child’s behavior, as well as potentially through an improvement in adherence to treatment following a psychoeducation course. Relatively few studies have looked at treatment adherence as an outcome, and this may be a future direction for researchers.